Charting the Course for Bureaucratic Reform: The Path to Progress in Purwakarta Regency - Iwan Satibi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The policy of preparing a bureaucratic reform road map for the Government of Purwakarta Regency is a strategic decision in line with the strengthening demands and needs of the community. The presence of an institutional bureaucratic reform road map has provided an opportunity for regional governments, including the Purwakarta Regency Government, to ensure the creation of improved governance. Comprehensively, the focus of changes in bureaucratic reform within the Purwakarta Regency Government includes 8 areas of bureaucratic reform, namely apparatus mentality, supervision, accountability, governance institutions, human resources for the state civil apparatus, laws and regulations, and public services. The results of the study found that in order to improve the quality of the policy road map for bureaucratic reform to be designed, there are three main things that must be updated, including; first, the road map for bureaucratic reform must project more on matters that are implementative in nature rather than matters that are merely formalities. Second, programs and activities that are designed must be realistic, so that they can be implemented up to work units. Third, policy analysis related to governance must be carried out in a more holistic, comprehensive and anticipatory manner so as to be able to capture real progress, challenges and problems of bureaucratic reform.